Design of Reversing Open Belt Transmission System for Salt-Crushing Machine with Roller-Type - Sutisna, Setya Permana; Siregar, Tika Hafzara; Sutoyo, Edi; Rahmat, Mamat; Setyawan, Gigih Bayu; Ridwan, Muhammad; Shah, Syed Humayon (Master Program in Mechanical Engineering, Gunadarma University, 2024)
The raw salt should be reduced the size to convert it into consumption salt. Salt crushing machine generally was designed to reduce salt grain size using rollers for crushing. The small-capacity salt-crushing machine should be designed to meet the needs of small businesses. This study aims to design a salt-crushing machine in a small capacity with a proper power transmission system that will be applied to a roller-type salt crusher. The transmission system is designed to upgrade the performance of roller-type salt crushers through V-belt and pulley transmission mechanisms and obtain the appropriate size or type of V-belt and pulley based on the capacity of the drive motor. The results show power required to crush salt by this system is 299.46 W. The motor used is a single-phase AC motor that has a power size of 1/2 HP, and the corresponding v belt is type A with a size of 51 inches, the rpm needed is 360 rpm, and the distance between rollers is 0,7 mm. Then the pulley needed is with a ratio of 1: 4. The pulleys used are type A1 which has a diameter of 3 inches and 12 inches. The average salt weight loss after the crushing process was 14.27%.